1993
DOI: 10.3171/jns.1993.78.2.0294
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral polyposis

Abstract: A 25-year-old man presented with nontraumatic cerebrospinal fluid rhinorrhea and meningitis. On investigation, he was found to have a multiloculated intracerebral cystic lesion of the right frontal lobe with a bony lesion inside the cyst, just above the right cribriform plate. Surgery revealed multiple grape-like cystic pedunculated lesions with narrow stalks attached to a bony outgrowth which was adherent to the right cribriform plate. Macroscopically and microscopically, the excised lesions were similar to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…continuity between the frontal sinus and the mucocele, and the aggressiveness of the association. Calcification of intracranial mucoceles is not rare 9,15) and histological evaluation of the bone tissue in mucoceles has been controversial. 10,15) However, histological assessment of the lesions in our cases showed that the mucocele materials contained bone islands (Figs.…”
Section: Fig 4 Case 2 Photomicrograph Showing Appar-mentioning
confidence: 99%
“…continuity between the frontal sinus and the mucocele, and the aggressiveness of the association. Calcification of intracranial mucoceles is not rare 9,15) and histological evaluation of the bone tissue in mucoceles has been controversial. 10,15) However, histological assessment of the lesions in our cases showed that the mucocele materials contained bone islands (Figs.…”
Section: Fig 4 Case 2 Photomicrograph Showing Appar-mentioning
confidence: 99%